2023
DOI: 10.1021/acsami.2c17560
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Recovered Ammonia and Carbon Dioxide into Urea in the Presence of Catalytically Active Copper Species in Nanospaces of Porous Silica Hollow Spheres

Abstract: The present study firstly reported porous silica hollow spheres as a host material for recovery of ammonia and carbon dioxide and conversion of the compounds into urea. These compounds were effectively introduced into the hollow spheres from an aqueous solution including ammonium and carbonate ions accompanied with catalytically active copper ions from the analyses of diffuse reflectance infrared Fourier transform (DRIFT) spectra and diffusion reflectance ultraviolet–visible and near-infrared (DR UV–vis-NIR) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…However, the particle size growth of the active ruthenium species was not observed on the ruthenium-encapsulated hollow silica spheres, as reported in another work. 40 The results displayed in Fig. 4 and 5 indicated that the activity of the ruthenium-encapsulated hollow silica sphere catalyst was mainly influenced by the dispersion of primary particles of the active metallic ruthenium species, and the particle size of the active species did not significantly change before and after the catalytic reaction.…”
Section: Resultsmentioning
confidence: 88%
“…However, the particle size growth of the active ruthenium species was not observed on the ruthenium-encapsulated hollow silica spheres, as reported in another work. 40 The results displayed in Fig. 4 and 5 indicated that the activity of the ruthenium-encapsulated hollow silica sphere catalyst was mainly influenced by the dispersion of primary particles of the active metallic ruthenium species, and the particle size of the active species did not significantly change before and after the catalytic reaction.…”
Section: Resultsmentioning
confidence: 88%
“…Otherwise, in the DTA curve of hollow silica spheres prepared with 1-dodecylamine (Figure a), the clear endothermic peak was not observed in the temperature range up to 373 K, while two peaks centered at 440 and 514 K assigned as phase transition and decomposition, respectively, of urea were observed. We previously reported that the yield of urea strongly depended on the size distributions of nanospaces of hollow silica spheres, and the amount of urea in the hollow silica spheres prepared with 1-dodecylamine (229 mg urea g-sample –1 ) with small size and narrow distribution of nanospaces was significantly high compared with those in the hollow spheres prepared with dodecane (76 mg urea g-sample –1 ) and 1-dodecanol (43 mg urea g-sample –1 ) . The results indicate that an appropriate amount of synthesized urea was required to identify thermochemical behaviors of the confined urea by DTA.…”
Section: Resultsmentioning
confidence: 92%
“…We previously reported that the yield of urea strongly depended on the size distributions of nanospaces of hollow silica spheres, and the amount of urea in the hollow silica spheres prepared with 1dodecylamine (229 mg urea g-sample −1 ) with small size and narrow distribution of nanospaces was significantly high compared with those in the hollow spheres prepared with dodecane (76 mg urea g-sample −1 ) and 1-dodecanol (43 mg urea g-sample −1 ). 13 The results indicate that an appropriate amount of synthesized urea was required to identify thermochemical behaviors of the confined urea by DTA. Otherwise, the peak temperatures in Figure 3c were higher than those of pristine urea.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 2 more Smart Citations